IMPLEMENTASI PERATURAN DAERAH KOTA SAMARINDA NOMOR 19 TAHUN 2001 TENTANG PENGATURAN DAN PEMBINAAN PEDAGANG KAKI LIMA TERHADAP PENYITAAN BARANG DAGANGAN PEDAGANG KAKI LIMA OLEH SATUAN POLISI PAMONG PRAJA KOTA SAMARINDA - Fathur Rizqi (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTThe polemic regarding urban planning for street vendors has become a problem that has occurred in the city of Samarinda. The Government of Samarinda City wants the city to look beautiful and neat but is constrained by the presence of street vendors that these street vendors sometimes violate regulations by not following the applicable regulations, therefore there are many violations such as street vendors selling on the sidewalks and on the side of the road. through the Civil Service Police Unit (Satpol PP) to take action. Satpol PP is a representative of the Government who has the task of enforcing local regulations and Satpol PP itself in carrying out its duties based on existing regulations and procedures, if it is not based on applicable regulations and procedures, Satpol PP has violated the rules.This study aims to determine the Implementation of Samarinda City Regulation Number 19 The year 2001 concerning Regulations and Guidance of Street Vendors relating to legal consequences if the Samarinda City Civil Service Police Unit when conducting seizures is not in accordance with the Standard Operating Procedure (SOP) and knows the procedure for returning goods street vendor merchandise that had been confiscated by the Samarinda City Civil Service Police Unit.The method used in this study is the Juridical Sociological (Empirical) research method, namely research conducted directly to review the location of the study. With the location of research at the Office of the Civil Service Police Unit of the City of Samarinda on Jalan Balaikota No.26 Kota Samarinda, East Kalimantan. The types and sources of data used are primary data and secondary data.Based on the results of the study that there were members of the Civil Service Police Unit in conducting the seizures not in accordance with the Operational Standard Procedure and not accompanied by Civil Servant Investigators (PPNS) even though the Civil Service Police Unit in charge must comply with the Standard Operating Procedure and be accompanied by Civil Servant Investigators in conducting control and seizure of street vendor merchandise because if it is not in accordance with the Operational Standard Procedure and not accompanied by Civil Servant Investigators will be subject to punishment as stipulated in Government Regulation Article (7) Number 53 of 2010 concerning Discipline of Civil Servants and for honorarium employees or with the term Employee The Government With Work Agreement (PPPK) will be charged according to the Laws and Regulations governing the Discipline of Civil Servants. Then the Samarinda City Civil Service Police Unit must understand the rules and still be guided by the SOP, and must continually continuously carry out their duties so that they do not become obscure and fundamental judgments by the community, especially street vendors regarding the intended confiscation.Keywords: Implementation, Regional Regulations, Foreclosures, Street Vendors, Civil Service Police Units